Update Study of Traded Birds at the Bird Shops in Jakarta - Septiana Anggraini Pratiwi; Fachruddin Majeri Mangunjaya; Tatang Mitra Setia (Universitas Nasional Jakarta, 2021)
The wild birds in nature can be threatened due to the increasing demand for birds for pets by some people. On the other hand, the bird trade can be an opportunity for gaining economic benefits. One of the highest demands of birds comes from Java, especially Jakarta. This study aims to determine the types of birds traded in bird shops in Jakarta along with their IUCN conservation status, the protection status according to the Ministry of Environment and Forestry Regulation No. 106 of 2018, and the CITES trading status. The research was conducted in April-May 2021. Data collection methods included direct observation (recording and recording) and interviews. The data were taken by purposively listing the bird shops. The data obtained were analyzed using qualitative descriptive analysis. The results show from sample area in Jakarta, we approached 57 bird traders (13 stores in Central Jakarta, 12 stores in North Jakarta, 12 stores in West Jakarta, 10 stores in East Jakarta, and 10 stores in South Jakarta). The birds found are coming from 42 bird families consisting of 117 species. 100 species are the least concern status, seven species are near threatened, one species is vulnerable, five species are endangered, and four species are critically endangered. Based on KLHK Ministerial Regulation No. 106 of 2018, there are 16 protected and 101 unprotected bird species. 113 bird species are not included in the CITES category, one species belongs to the appendix I category, three species belong to the appendix II category. Although in general the IUCN status of the traded birds is LC, a large number (73%) of the wild bird species were caught from nature. The survey shows the trend of the bird trade together with the increasing market demand may lead to population decline that caused rareness of the species and perhaps extinction.